PENGARUH KOMPOSISI PERBANDINGAN DAN WAKTU PERAWATAN DENGAN MENGGUNAKAN AIR LAUT TERHADAP KUAT TEKAN MORTAR - Latifah, Evi; Zulfa, Naila; Rokhmawati, Tri Indah; Tisnawati; Kumalasari, Dwi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
A mortar is a combination of fine aggregate (usually sand), an adhesive (usually cement), and water (usually in a certain proportion). Mortar is used as a coating for outside walls in non-structural constructions, and as a species for walls and foundations in structural constructions. The purpose of this study is to analyze the impact of sea water on the compressive strength of mortar when treated using various ways. This study follows SNI 03-6825-2002 for producing and evaluating mortar's compressive strength using a 1:3 and 1:4 mortar mixture ratio. The cube-shaped mortar test item has a circumference of 5 cm x 5 cm x 5 cm and contains 36 samples in total. For treatment ages of seven, fourteen, or twenty-eight days of therapy, saltwater and artesian well water are used to soak mortar. At the 28-day mark, the compressive strength of mortar with a 1:3 ratio of artesian well water to sea water reaches 33.1 MPa and 25.5 MPa, respectively. An increase in compressive strength was seen with increasing age in the 1:3 mixture composition, but a reduction was observed at 14 days in the 1:4 mixture composition using artesian well water and sea water.